Relationship between working capital management and firm profitability: evidence from plantation sector in Malaysia / Azean Kamal - Kamal, Azean (Faculty of Business Management, 2018)
Working capital management (WCM) is usually observed as one of the contributing factors of certain firms' profitability. Mainly, the ultimate goal of any business is to make a profit so that the business can continue operating for a long run. The management of working capital plays an important role in firm profitability in order to sustain its growth. Numerous findings mentioned that WCM has a positive relationship with firm profitability. However, some papers found a negative relationship between them. Moreover, the chosen tested variables also found mixed results by the past researchers, where some found a negative relationship between each independent variable and dependent variable and vice versa. Thus, these relationships have onen been debated as it has been remarked over time, that working capital management does give a significant effect towards firm profitability. This study was carried out to establish the relationship between WCM and firm profitability from plantation sector in Malaysia. This research was done on 40 companies registered in Bursa Malaysia, which covered the period of 2013 — 2017 with a total observation of 200 firms/years. The independent variables to measure working capital management include cash conversion cycle, current ratio, debt ratio and sales gowth while, return on asset acts as a proxy for the dependent variable, firm profitability. The collected data was analyzed using descriptive means, correlation analysis and multiple linear regressions via E-Views. Ordinary Least Squares (OLS) method and Multiple Linear Model (MLRM) were used in this research to examine the relationship between WCM and the profitability of the firms. From this study, current ratio and debt ratio are found to have a negative significant relationship with firm profitability, while, sales yowth has a positive significant relationship with firm profitability.